Patient consultations during SARS-CoV-2 pandemic: a mixed-method cross-sectional study in 16 European countries - Petrazzuoli, Ferdinando; Gokdemir, Ozden; Antonopoulou, Maria; Blahova, Beata; Mrduljaš-Đujić, Natasa; Dumitra, Gindrovel; Falanga, Rosario; Ferreira, Mercedes; Gintere, Sandra; Hatipoglu, Sehnaz; Jacquet, Jean-Pierre; Javorská, Kateřina; et al. (Rural and remote health, 2022)
INTRODUCTION: Remote consultations help reduce contact between people and prevent cross-contamination. Little is known about the changes in consultation in European rural primary care during the SARS-CoV-2 (COVID-19) pandemic. The purpose of this mixed-methods cross-sectional study was to find out more about the effects of the pandemic on changes in patient consultations in European rural primary care. METHODS: A key informant survey from 16 member countries of the European Rural and Isolated Practitioners Association (EURIPA) was undertaken using a self-developed questionnaire. The steering committee of this project, called EURIPA Covid-19 study, developed a semi-structured questionnaire with 68 questions, 21 of which included free-text comments. Proportions were calculated for dichotomized or categorized data, and means were calculated for continuous data. Multivariate analysis by logistic regression model was used to assess the association of multiple variables. RESULTS: A total of 406 questionnaires from primary care providers (PCPs) in 16 European countries were collected; 245 respondents (60.5%) were females, 152 PCPs were rural (37.5%), 124 semi-rural (30.5%). Mean age of the respondents was 45.9 years (standard deviation (SD) 11.30) while mean seniority (length of experience) was 18.2 years (SD 11.6). A total of 381 (93.8%) respondents were medical doctors. Significant differences were found between countries in adopting alternative arrangements to face-to-face consultation: remote teleconsultation is well appreciated by both healthcare professionals and patients, but the most common way of remote consultation remains telephone consultation. A factor significantly inversely associated with the adoption of video consultation was the seniority of the PCP (odds ratio 1.19, 95% confidence interval 1.02-1.40, p=0.03). CONCLUSION: Telephone consultation is the most common form of remote consultation. The adoption of video-consultation is inversely related to the seniority of the informants.
Keywords: Telemedicine; pandemie; Humans; lidé středního věku; telephone consultation; konzultace na dálku; Female; Pandemics; lidé; COVID-19; telemedicína; ženské pohlaví; consultation; Male; Middle Aged; access to care; Cross-Sectional Studies; Remote Consultation; telemedicine; mužské pohlaví; SARS-CoV-2; průřezové studie; Telephone; primary care; telefon